PENGARUH SENAM LANSIA TERHADAP TEKANAN DARAH PADA LANSIA HIPERTENSI DI PUSKESMAS WALANTAKA - Rina Puspita Sari; Eti Nurhayati Kamil (Jurnal Kesehatan, 2017)
Blood pressure will increase after the age of 45- 55 years, the arterial wall will be thickened by the accumulation of collagen substances in the musclu layer, so that the blodd vessels will gradually narrow to become stiff. Elderly gymnastics is a mild exercise and easy to do, not burdensome, wich is applied to the elderly. The purpose of this study was to analiyze the influence of elderly gymnastics on blood pressure in elderly hyperention at Walantaka Community Health Care. The design used in this study was” quasi experimental non equivalent pretest-postest control group design “ with elderly gymnastic intervention”. The sample size was 72 elderly divided intoi 2 groups, intervention group 36 elderly and control group 36 elderly. Analysis using t test. Result of research : There is influence of elderly gymnastics to blood pressure in elderly hypertention in Puskesmas Walantaka (P value 0,001). Suggestion : Health worker need to do socialization and training of elderly gymnastics implementation skills so that it can carry out the management of elderly who experience hypertention by non farmakologi management ti control blood pressure in hypertention patient.